New insights into the role and mechanism of c‐Jun‐N‐terminal kinase signaling in the pathobiology of liver diseases. Issue 5 (6th April 2018) - Win, Sanda; Than, Tin Aung; Zhang, Jun; Oo, Christina; Min, Robert Win Maw; Kaplowitz, Neil
Abstract : The c‐Jun‐N‐terminal‐kinase (JNK) family is highly conserved across species such as Drosophila, C. elegans, zebrafish and mammals, and plays a central role in hepatic physiologic and pathophysiologic responses. These responses range from cell death to cell proliferation and carcinogenesis, as well as metabolism and survival, depending on the specific context and duration of activation of the JNK signaling pathway. Recently, several investigators identified the key molecules in the JNK activation loop which include apoptosis signal‐regulating kinase (ASK1) and SH3‐domain binding protein 5 (Sab) and their involvement in acute or chronic liver disease models. Thus, regulating JNK activation through modulating the JNK activation loop may represent an important new strategy in the prevention and treatment of acute and chronic liver diseases. In this review, we will discuss the molecular pathophysiology of the JNK activation loop and its role in the pathogenesis of liver diseases. (Hepatology 2018;67:2013‐2024).